(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
The anticancer activity of resveratrol is well known. But because of its limited water solubility and low bioavailability, resveratrol (RES) is a BCS class II medication with research potential. The current work creates a new copolymer from Lipoid S-75 and chitosan and tests the RES-loaded micelles it produces for varied delivery properties. In addition to efficiently loading the drug, the nanometric micellar carriers also regulated the rate of RES release. The discoveries using a novel polymer-based carrier show promise for improved medication delivery in the future. Aim: The aim of the study was to synthesize and characterize the lipoid S-75 conjugated chitosan-based micelles for improving biopharmaceutical parameters of resveratrol. Methods: The preparation and characterization of a copolymer of CS and lipoid S-75 were done by using S-75 100 mg and DCC 700 mg which is followed by preparation and characterization of CS-lipoid S-75-conjugated resveratrol micelles. And evaluation of the formulation done by the parameters such as particle size, polydispersity index zeta potential, % encapsulation efficiency and drug loading, drug loading capacity, and differential scanning calorimetry. Results: In the present study, development of polymeric micelles using the flavonoid in multifaceted applications, entailing therapy, diagnostics, in-suit imaging, and on-demand drug delivery, resveratrol, polymers such as chitosan, and lipoid S-75 show significant potential. The fundamental formation mechanisms are then analyzed, focusing on the inherent physicochemical qualities like solubility and bioavailability that control the drug release. Conclusion: The development of resveratrol-loaded chitosanbased S-75 micelles demonstrates considerable potential for multifaceted biomedical applications, including therapy, diagnostics, in-situ imaging, and on-demand drug delivery. The combination of resveratrol, chitosan, and lipoid S-75 results in a polymeric micellar system with enhanced solubility and bioavailability, addressing the challenges associated with the poor aqueous solubility and rapid metabolism of resveratrol. The analysis of the micelle formation mechanisms highlights the crucial role of the inherent physicochemical properties in controlling drug release. This innovative micellar platform offers promising avenues for optimizing the therapeutic delivery of resveratrol and broadening its application scope in pharmaceutical and biomedical fields.